2012
DOI: 10.1116/1.4732460
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of an electrical spin transport device utilizing a diazonium salt/hafnium oxide interface layer on epitaxial graphene grown on 6 H-SiC(0001)

Abstract: Nonlocal Hanle spin precession devices are fabricated on wafer scale epitaxial graphene utilizing conventional and scalable processing methods. To improve spin injection and reduce contact related spin relaxation, hafnium oxide is utilized as an interface barrier between the graphene on SiC(0001) and ferromagnetic metal contacts. The hafnium oxide layer is deposited by atomic layer deposition utilizing an organic seed layer. Spin precession is observed in the epitaxial graphene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…To prevent this mismatch high resistive barriers between the contacts and the graphene channel are included 4,[19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent this mismatch high resistive barriers between the contacts and the graphene channel are included 4,[19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…To prevent this mismatch, high resistive barriers between the contacts and the graphene channel are included. 4,[19][20][21][22][23] The most common and reliable way to probe spin transport properties is by performing measurements in the nonlocal spin valve geometry 2,5,24 because it enables the separation of spin and charge currents, avoiding spurious effects. 25 Popinciuc et al 19 describe, in agreement with Takahashi and Maekawa,26 that the measured amplitude of the spin signal in the nonlocal geometry is strongly reduced for low contact resistances R C .…”
Section: Introductionmentioning
confidence: 99%
“…Here R sq is the square resistance, e the electron charge and ν(E F ) the density of states (DOS) of the diffusive channel at the Fermi energy. Spin transport in graphene has been extensively studied in recent years [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Due to weak spin-orbit coupling g = 2 is commonly assumed to fit Hanle precession data (and define c) [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
mentioning
confidence: 99%
“…Spin transport in graphene has been extensively studied in recent years [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Due to weak spin-orbit coupling g = 2 is commonly assumed to fit Hanle precession data (and define c) [3][4][5][6][7][8][9][10][11][12][13][14][15]. This was justified for exfoliated single layer graphene (eSLG) as it was shown that D ≈ D C [5].…”
mentioning
confidence: 99%
“…4 In addition, it has become an attractive material for use in spintronic devices owing to its long electron spin relaxation time at room temperature. [5][6][7] This arises in part from its low spin-orbit coupling and negligible nuclear hyperfine interaction. 1, [8][9][10] A typical graphene based device fabrication process includes: spin coating of photoresist, electron beam lithography, metal or dielectric deposition, and lift-off of excess deposited layers.…”
Section: Introductionmentioning
confidence: 99%